OPTIMALISASI LAYANAN KESEHATAN IBU DAN ANAK MELALUI PROGRAM TANGGAP BENCANA HIDROMETEOROLOGI PADA MASYARAKAT TERDAMPAK BANJIR BANDANG DI KABUPATEN AGAM - Rinita Amelia; Ira Suryanis; Dessy Abdullah; Yudha Endra Pratama; Harnavi Harun; Sari Setiarini; Afrah Diba Faisal (Yayasan Nusantara Hasana Berdikari, 2025)
Hydrometeorological disasters such as flash floods significantly impact access to and quality of health services, particularly for vulnerable groups such as pregnant women, postpartum mothers, breastfeeding mothers, infants and toddlers. Agam Regency, West Sumatra, is one of the areas affected by flash floods, with the risk of disruption to maternal and child health services. This Community Service (PKM) activity aims to optimize maternal and child health services through a hydrometeorological disaster response program for communities affected by flash floods in Agam Regency. The activity uses a descriptive-participatory approach, implemented through preparation, implementation, monitoring, and evaluation. The activities include comprehensive midwifery services, health services, maternal and child health education, and basic psychosocial support. The results of the activity indicate that the PKM program can improve access to maternal and child health services and achieve a high level of participant satisfaction. This activity is considered beneficial and appropriate to the needs of disaster-affected communities. This program is expected to become a model of applicable and sustainable community service in supporting maternal and child health services in hydrometeorological disaster situations.